DECISION SUPPORT SYSTEM PERUSAHAAN MANUFACTURING DALAM MENENTUKAN PEMASOK MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Hartono, Henny; Andry, Johanes Fernandes; Liebe Imbing, Berliana Glorya; Gunawan, Catherine (Infotech: Journal of Technology Information, 2019)
Suppliers are one of the important things in purchasing activities of various needs for the company. Supplier selection is a multi-criteria problem that includes quantitative and qualitative factors. One method that can be used for supplier selection is the Analytical Hierarchy Process (AHP) method. This research was conducted at Manufacturing companies in relations with suppliers who will develop a partnership relationship between companies and suppliers. The purpose of this research is that the right supplier can help the company in increasing competitiveness that can increase company revenue. To help companies choose the right supplier, a decision support system is needed. The variables used in this paper are price, quality, service, delivery accuracy and quantity. The most determining criterion in selecting suppliers is the accuracy of delivery criteria, making these criteria a major factor in supplier selection. The results of this study are consistency in delivering goods on time and guaranteeing safety in guaranteeing the quality of a product.